THE KNOWLEDGE OF THE LOCAL COMMUNITY IN THE BUFFER ZONE OF THE BUKIT RIMBANG BUKIT BALING WILDLIFE RESERVE ABOUT STINGLESS BEE CULTIVATION (Trigona spp.) - Fariz Hidayat; Nurul Qomar; Yossi Oktorini (Jurusan Kehutanan Fakultas Pertanian Universitas Riau, 2020)
Bukit Rimbang Bukit Baling Wildlife Reserve (BRBB) was designated in 1982 and was established in 2014 based on the Decree of the Minister of Forestry SK Number. 3977 / Menhut-VIII / KUH / 2014 dated May 23, 2014 covering an area of 141,226.25 ha in Kampar Regency and Kuantan Singingi Regency, Riau Province. The aim of this study was find out about local community knowledge in the Wildlife Conservation Area (BRBB) about kelulut or stingless bee (Trigona spp.) cultivation and to know the relationship between the respondent characteristics with that knowledge. This method of this research was quantitative approaches. The number of respondents was 85 people, selected based on random sampling spread in Koto Lamo Village, Bukit Betung Village, and Tanjung Belit Selatan Village. Data were analyzed statistically by chi-square test. The results of this study show that the local community has knowledge about stingless bee cultivation at the “knowing” level. Individual factors that were significantly related to people's knowledge of stingless bee cultivation were gender, employment, and education.